2021
DOI: 10.1039/d0ra10625a
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo in situ construction of high-performance thermoelectric composites with a dioxothiopyrone-based D–A polymer coating on SWCNTs

Abstract: High-performance thermoelectric composites with a dioxothiopyrone unit have been constructed utilizing SWCNTs and polymer TPO-TTP12via a simulated in situ compositing strategy based on the coagulation method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…Thus, we concluded that the incorporation of the Te nanocrystals can significantly improve the S of PPy materials. The reasons why the PPy/Te composites can maintain relatively large S values were analyzed as follows: (1) the homogeneous and dense coating of the PPy on the Te surface forms a good interfacial contact and produces the effective electron energy filtering effect that can block the transport of low-energy carriers to a certain extent and offsets partially the declining of the S due to the introduction of PPy; 45 (2) the ultrathin coverage of PPy does not change the predominant role of Te in determining the S values of the composites, although this can compromise partial contribution of Te to the S. Accordingly, an array of PPy/Te composites with S values of above 100 μV K −1 were achieved, which are at least twice as high as that of the PPy materials treated by electrochemical de-doping. 17 Certainly, it must be pointed out that, the S values of the PPy/Te composites would go down gradually up to approaching the value of the oxidative PPy as the deposition time continues to prolong.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we concluded that the incorporation of the Te nanocrystals can significantly improve the S of PPy materials. The reasons why the PPy/Te composites can maintain relatively large S values were analyzed as follows: (1) the homogeneous and dense coating of the PPy on the Te surface forms a good interfacial contact and produces the effective electron energy filtering effect that can block the transport of low-energy carriers to a certain extent and offsets partially the declining of the S due to the introduction of PPy; 45 (2) the ultrathin coverage of PPy does not change the predominant role of Te in determining the S values of the composites, although this can compromise partial contribution of Te to the S. Accordingly, an array of PPy/Te composites with S values of above 100 μV K −1 were achieved, which are at least twice as high as that of the PPy materials treated by electrochemical de-doping. 17 Certainly, it must be pointed out that, the S values of the PPy/Te composites would go down gradually up to approaching the value of the oxidative PPy as the deposition time continues to prolong.…”
Section: Resultsmentioning
confidence: 99%